Age at the diagnosis and in the beginning of intervention from hearing impaired children, in a public Brazilian hearing health service - Pinto, Meliane Melina; Raimundo, Jeziela Cristina; Samelli, Alessandra Giannella; de Carvalho, Ana Claudia Martinho; Matas, Carla Gentile; Ferrari, Gisele Munhoes dos Santos; Garbi, Sérgio; Gândara, Mara; Bento, Ricardo Ferreira (Arquivos Internacionais de Otorrinolaringologia, 2012)
Introduction: The earlier the diagnosis and the intervention from the hearing impairment less will be the impact for the development of cognitive abilities, hearing and of speech from the child.Objective: Characterize the age in the diagnosis and the beginning of intervention of the hearing loss and the accompaniment of the assisted children in a public Brazillian hearing health service – Espaço Reouvir from the Clinicas Hospital from the Medical School from the University of São Paulo.Method: Retrospective study with information from 166 medical records from children regarding the: gender; etiology, type, degree and laterality of the hearing impairment; age in the diagnosis and adaptation of the Hearing aids (HA) and accompaniment in the service.Results: The sample was composed by 56% men and 44% women. The prevailing etiology was from multifactorial origin. The hearing loss from the neurosensory type occurred in 88,6% of the cases. The degree of moderate hearing loss was the most frequent (30,7%), symmetry in both ears was found in 69,9% of the cases and unilateral hearing loss in 2,4%. The average age in the diagnosis was of 5,46 years and in the intervention was of 6,86 years. A total of 96,98% of children had already completed the process of adaptation and 78,32% still remained in the accompaniment.Conclusion: The program Reouvir-HCFMUSP still receives children, both for diagnosis and or intervention in a late manner. However, still is possible the realization of the accompaniment of a significant number of users of the hearing aids, enabling a process of adaptation more effective.
Keywords: hearing; auxiliary of hearing; children; hearing loss